Penguatan Literasi Digital sebagai Upaya Mengurangi Risiko Kejahatan Siber di Desa Pacarejo, Kecamatan Semanu, Kabupaten Gunungkidul - Anam, Ahmad Muzakkil; Agustinova, Danang Ade; Rokhim, Hanif Nur; Dhewantoro, Happri Novriza Setya (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2025)
The increasing development of internet access and the penetration of digital devices has had a significant impact on rural communities, enabling them to connect within the digital ecosystem. However, the low level of digital literacy among them has also increased their potential to become victims of cybercrime. This cybercrime not only causes material losses but also threatens individual security and privacy, as well as disrupts the social and economic stability in rural areas. Therefore, the protection and enhancement of digital literacy become essential preventive measures to reduce these risks. This community service program aims to improve digital literacy through socialization, education on various forms of cybercrime, training on measures to anticipate cybercrime, and practical use of anti-cybercrime applications on smartphones. With this program, it is hoped that Pacarejo Village can become a model in building local cyber resilience, which in turn can reduce the risk of cybercrime and enhance the digital security and well-being of the village community